The Effect of Corporate Social Responsibility (CSR), Institutional Ownership, Leverage, And Firm Size on Financial Performance - Rita Kusumawati; Faradila Puteri Findasari (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
Financial performance is a determining indicator of the sustainability of the firm. To run according to the goals, companies need to analyze factors that can affect financial performance, such as social responsibility, corporate governance, leverage, and firm size. Through CSR and serious corporate governance, it can improve financial performance. This study examines the influence of CSR, Institutional Ownership, Leverage, Firm Size, and the role of Earning Management on the Financial Performance (ROE) of manufacturing companies listed on the IDX in 2017-2021. The test results using SPSS 23 found that CSR, Institutional Ownership, Leverage, and Firm Size affected financial performance, earning management moderates the relationship between CSR and financial performance